Possession in Martuthunira - Dench, Alan (2013)
© Editorial matter and organization Alexandra Y. Aikhenvald and R. M. W. Dixon 2013 © The chapters their several authors 2013. All rights reserved. This chapter offers a comprehensive analysis of expression of possession and of ownership in Martuthunira, an extinct Australian language, formerly spoken in the Plibara region of Northern Australia. Pertensive, proprietive are employed to express possessive relationships. Genitive is used for some types of possession, and some kinship relations. Privative is a way of marking negative possession. Part-whole relationship is coded by simple apposition. There are no verbs of possession: possession can be coded through verbs meaning 'grab', 'catch' and 'hold'. The patterns of distribution of possessive marking in Martuthunira reflect the importance of kin relationships. There is a strong cultural distinction between close, or 'dear', kin, and more distantly related relatives. The 'dear' kin stand in contrast to the wider network of more distant classificatory kin in terms of their linguistic marking, and societal status.